2013
DOI: 10.1038/gene.2013.62
|View full text |Cite
|
Sign up to set email alerts
|

HLA-DPB1 and anti-HBs titer kinetics in hepatitis B booster recipients who completed primary hepatitis B vaccination during infancy

Abstract: Previously we reported significant associations of the human leukocyte antigen (HLA)-DPB1 05:01 with memory against hepatitis B (HB) vaccination. However, the effects of HLA-DPB1 on antibodies to hepatitis B surface antigen (anti-HBs) kinetics were not explored. We followed up a cohort of 1974 HB booster recipients and quantified their 1-month and 1-year post-booster anti-HBs titers. A total of 681 subjects were randomly selected and typed for HLA-DPB1. We found that male subjects, undetectable pre-booster tit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…HLA-DPB1*05:01 has also been shown to be more common in individuals who do not develop seroprotection after hepatitis B vaccination. 56 We also observed consistent associations of HLA class I alleles HLA-A*11:01, HLA-B*35:03, and HLA-B*51:01 (predisposing) after correction of all HLA class II effects, suggesting an independent role for these HLA alleles. These findings are similar to those found in other autoimmune diseases, such as MS 32,57,58 or type 1 diabetes, 59 where the main risk alleles are located in the HLA class II region but residual association is seen in HLA class I.…”
Section: Discussionsupporting
confidence: 55%
“…HLA-DPB1*05:01 has also been shown to be more common in individuals who do not develop seroprotection after hepatitis B vaccination. 56 We also observed consistent associations of HLA class I alleles HLA-A*11:01, HLA-B*35:03, and HLA-B*51:01 (predisposing) after correction of all HLA class II effects, suggesting an independent role for these HLA alleles. These findings are similar to those found in other autoimmune diseases, such as MS 32,57,58 or type 1 diabetes, 59 where the main risk alleles are located in the HLA class II region but residual association is seen in HLA class I.…”
Section: Discussionsupporting
confidence: 55%
“…Further large-scale studies are required to provide more concrete data. Nevertheless, the results of this study may be incorporated into other research to broaden the understanding of the immune response of the HBV vaccine among young Taiwanese adults (24,34,40). Third, as a result of limited funding, we did not test HLA-DR, despite extensive studies both domestically and internationally (20,23,(26)(27)(28)(29) reporting a strong linkage disequilibrium between HLA-DR and -DQ alleles.…”
Section: Discussionmentioning
confidence: 99%
“…HLA-DRB1 *11, HLA-DQB1 *0301 and HLA-DRB1 *07 were found to be associated with HCV clearance or persistence, and HLA-DPA1 *0103, HLA-DPB1 *0402 and HLA-DPB1 *0501 were found to be candidate predictive factors for antibody production after HBV vaccination [51,52,53]. Moreover, Bain et al previously identified a specific CD8 + memory T cell response for HLA-A2 and/or HLA-B7 predicted epitopes derived from the HCV F protein in patients with HCV natural infection [16].…”
Section: Resultsmentioning
confidence: 99%